Cold tolerance of forage legumes growing in controlled continental Mediterranean conditions - Sánchez-Díaz M.; Hekneby M.; Antolín M.C. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
The growth of forage crops in Mediterranean areas is seriously limited by the dry summer but also by the cold winter. Potential forage species should be tested to improve the forage availability in these periods in which herbage production is limited. The objectives of this study were to compare seedling survival and viability in response to cold conditions and to identify ecophysiological mechanisms of cold response in annual legumes cultivated in Mediterranean zones. Experiments were carried out in several annual forage legumes (Trifolium brachycalycinum, T. michelianum, Medicago polymorpha, M. truncatula and M. scutellata) that were compared with some annual grain legumes (Vicia ervilia, V. narbonensis, V. articulata and Pisum sativum) and with some perennial forage legumes (Medicago sativa, Hedysarum coronarium and Onobrychis viciaefolia).
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)